Sugarcane bagasse as a co-substrate with oil-refinery biological sludge for biogas production using batch mesophilic anaerobic co-digestion technology: Effect of carbon/nitrogen ratio - Ghaleb A.A.S.; Kutty S.R.M.; Salih G.H.A.; Jagaba A.H.; Noor A.; Kumar V.; Almahbashi N.M.Y.; Saeed A.A.H.; Saleh Al-dhawi B.N. (MDPI AG, 2023)
Bagasse; Biogas; Biological water treatment; Carbon; Delignification; Liquid methane; Methane; Petroleum refineries; Sewage treatment plants; Sludge digestion; Sodium hydroxide; Substrates; Wastes; Wastewater treatment; Anaerobic co-digestion; Anaerobic digestion technology; Batch experiments; Biogas and methanes; Biological sludge; Solid-liquid ratio; Sugar-cane bagasse; Wastewater treatment plants; Anaerobic digestion; activated sludge; anaerobic digestion; biogas; biotechnology; carbon isotope ratio; crop residue; experimental study; industrial production; nitrogen isotope; organic pollutant; substrate